Konsepsi Pendidikan Katolik Menurut Dokumen Mendidik di Masa Kini dan Masa Depan Semangat yang Diperbarui (Instrumentum Laboris) - Bhakti, Angga Satya (Vocat : Jurnal Pendidikan Katolik, 2024)
Catholic education is an understanding of education that is imbued with Christian spirituality. It can take the form of managing educational institutions such as Catholic schools and colleges; Catholic Religious Education can also be a means of providing subjects and courses in the realm of Catholic religion. The Catholic Church is an institution that considers education as a means of preaching with a clear concept. The rules, meaning, and perspectives of Catholic education are very important. Documents of the Church such as the Gravisimus Educationis, the Book of Canon Law, and Educating  Today and  Tomorrow: A Renewing   Passion (Instrumentum Laboris) provide evidence of the Church's attention to education. The purpose of this study is to reconsider the conception of education from the perspective of the Church in particular. The conception of Catholic Education must be able to act contextually by paying attention to various challenges such as the development of the times and establish cooperation with various parties